Formulasi Dan Evaluasi Fisik Sediaan Salep Dari Variasi Ekstrak Buah Delima (Punica Granatum L.) - Usman, Wilda Fhitriany; Widianti, Reika Aqni; Shaleh, Aries Badrus (Jurnal Farmasi & Sains Indonesia, 2024)
Pomegranate is one of the fruits mentioned by Allah in the Koran and has many health benefits. In the Qur'an, Allah calls it al-rumman or what we usually call pomegranate. Red pomegranate (Punica granatum L.) contains flavonoids and phenols which are thought to be effective as antibacterials. The ointment is a semi-solid preparation that is easy to apply and is used as an external medicine, has direct access to the tissue and has greater aesthetic value. In this study, ointment preparations were formulated with variations of red pomegranate extract (Punica granatum L.) and propylene glycol in 7 ointment formulas. The evaluation tests carried out were organoleptic tests, spreadability tests, adhesiveness tests, pH tests, viscosity tests, stability tests and hedonic tests. The optimum preparation uses Simplex Lattice Design (SLD). The results of the physical evaluation of 7 formulas for various ointment preparations of pomegranate extract weighing 100 grams using PEG 400 and PEG 4000 bases and also the comparison of Propylene Glycol showed that 1 optimum formula was close to the recommended concentration based on the results of analysis using SLD, namely formulas 1 & 7 with concentration of pomegranate extract 5% and Propylene glycol 2% with 3 replications of the test. The evaluation results obtained were a semi-solid ointment evaluation test, typical rose smell, homogeneous, pH value 5.22, adhesion test 6.57 seconds, spreadability test 2.8 & 2.5 cm, viscosity test 3612 & 3611